Pengaruh Adanya Restrukturisasi Kredit Terhadap Perilaku Pembayaran Kewajiban Umkm dalam Masa Pandemi Covid-19 Kabupaten Pesisir Selatan Tahun 2020 - Ananda, Patrio; Rina Asmeri; Sri Yuli Ayu Putri (Fakultas Ekonomi, Universitas Ekasakti, 2023)
This study discusses the Effect of Credit Restructuring on repayment capacity of UMKM the Covid-19 Pandemic in Pesisir Selatan Regency. The sample selection technique used strata sampling with a percentage level of 2% from each strata area and obtained as many as 113 UMKM as samples. Data processing in this study is to use a simple regression model using SPSS 21.0 The results of the analysis of this study indicate that the regression of the credit restructuring variable is 0.655, meaning that if the credit restructuring is increased by one unit of weight, it will result in an increase in Credit Restructuring on repayment capacity of UMKM the Covid-19 Pandemic of 0.655. In the hypothesis test, the credit restructuring variable (X) with a tcount value of 10.311 > ttable 1.65870 and a significant level of 0.000 <0.05 and, it can be concluded that Ho is rejected and H1 is accepted, meaning that credit restructuring (X) partially has a positive and significant effect. on the effect of UMKM in repayment capacity (Y) to UMKM in the South Coast. The contribution of the independent variable of credit restructuring (X) to the dependent variable, namely the behavior of MSMEs in paying obligations, is 0.489 or 48.9%. While the remaining 0.511 or 51.1% is influenced by other variables outside the study.